Model and Construction of Islamic Education Curriculum : In Thamavitya Mulniti School Muang Yala Thailand - Roqib, Moh; Sugiarti, Iis; Chehae, Abdulghani (Jurnal Educative: Journal of Educational Studies, 2021)
Historically Patani was an independent kingdom. However, it is now part of the Kingdom of Thailand. This creates dilemmas and various conflicts, including in regard to Islamic education. In this study the author will examine the model and curriculum construction of Islamic Education in the Thamavitya Mulniti School Muang Yala, Southern Thailand. This is a qualitative research using interview, observation and documentation techniques in extracting data. This study shows that, genealogically, the Thamaviya Mulniti School departs from the Islamic Boarding School (Pesantren), which is then complementary to the formal education system. The education model in Thamavitya Mulniti School uses traditional and modern education models. In formal education, the school applies a system of religious classes and academic classes which are carried out separately. Curriculum construction in the school is the application of a dualistic curriculum, namely religious and academic at the discretion of the Thai Government. The religious curriculum includes subjects of Islamic Religious Education, as well as Malay language and culture. Academic curriculum includes general subjects (science). This curriculum model has implications for the level of progressivity of Islamic education, especially if it is associated with historical and geopolitical conditions. The Patani Muslim community with regard to Islamic education experiences a dilemma, between hegemony, global demands in maintaining culture as a national identity.Menurut sejarahnya dahulu Patani merupakan kerajaan yang berdiri sendiri dan mandiri yang sekarang telah masuk ke dalam kekuasaan Kerajaan Thailand. Akibatnya timbul dilema dan konflik di berbagai bidang, termasuk dalam bidang pendidikan Islam. Pada penelitian ini penulis akan mengkaji tentang model dan konstruksi kurikulum Pendidikan Islam di Thamavitya Mulniti School Muang Yala Thailand Selatan. Penelitian ini merupakan penelitian kualitatif dengan menggunakan teknik wawancara, observasi dan dokumentasi dalam penggalian datanya. Hasil penelitian menunjukkan bahwa secara genealogis Thamavitya Mulniti School merupakan sekolah yang berangkat dari pendidikan pesantren yang kini mengkomplementerkan dengan sistem pendidikan formal. Model pendidikan di Thamavitya Mulniti School Muang Yala Thailand menggunakan model pendidikan tradisional (pesantren) dan pendidikan modern (formal). Pada pelaksanaan pendidikan formal menerapkan sistem kelas yang terpisah antara kelas agama dan kelas akademik. Konstruksi kurikulum di sekolah menerapkan kurikulum dualistik yaitu agama dan akademik (sains). Kurikulum agama meliputi mata pelajaran rumpun Pendidikan Agama Islam termasuk Bahasa, dan Budaya Melayu. Kurikulum akademik meliputi mata pelajaran pengetahuan umum. Dengan adanya kebijakan penggunaan kurikulum tersebut berimplikasi terhadap progresivitas pengembangan pendidikan Islam. Terutama jika dikaitkan dengan kondisi historis dan geopolitikÂ  menyebabkan masyarakat Muslim Patani mengalami dilema, antara hegemoni, tuntutan global dan dalam mempertahankan budaya sebagai identitas bangsa.